(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
The interaction of analginum anion with dye of triphenilmethane brilliant green has been studied. Formed ionic associate could be removed once shot extraction (R=0.96) by dichlorethane–amylacetate (1:2) binary mixture in pH 1 (H2SO4) solutions. The extracts of ionic associate are submited with the main law of spectrophotometer in the 0.9–20 mcg/mL range of analginum contents ( ε =2.3 ⋅104 L⋅mol⋅cm). The elaborated method has been applied for determination of analginum in baralgetase, spasmalgonum and benalginum. In the case of tempalgin low results have been received.